Skewed X-Chromosome Inactivation Is a Common Feature of X-Linked Mental Retardation Disorders - Plenge, Robert M. (The American Society of Human Genetics, 2002)
Some deleterious X-linked mutations may result in a growth disadvantage for those cells in which the mutation, when on the active X chromosome, affects cell proliferation or viability. To explore the relationship between skewed X-chromosome inactivation and X-linked mental retardation (XLMR) disorders, we used the androgen receptor X-inactivation assay to determine X-inactivation patterns in 155 female subjects from 24 families segregating 20 distinct XLMR disorders. Among XLMR carriers, ∼50% demonstrate markedly skewed X inactivation (i.e., patterns ⩾80:20), compared with only ∼10% of female control subjects (P<.001). Thus, skewed X inactivation is a relatively common feature of XLMR disorders. Of the 20 distinct XLMR disorders, 4 demonstrate a strong association with skewed X inactivation, since all carriers of these mutations demonstrate X-inactivation patterns ⩾80:20. The XLMR mutations are present on the preferentially inactive X chromosome in all 20 informative female subjects from these families, indicating that skewing is due to selection against those cells in which the XLMR mutation is on the active X chromosome.